2007
DOI: 10.1016/j.tcm.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Heart Function and Aging in Drosophila

Abstract: Why is Drosophila a good model of cardiac physiology?The fly heart has been an excellent model of cardiovascular development for over a decade. Since the discovery of the homeobox transcription factor tinman (Azpiazu and Frasch 1993, Bodmer 1993, Bodmer et al. 1990) and the recognition that it is conserved in vertebrates [reviewed in (Bodmer 1995, Harvey 1996], more and more evidence has corroborated the idea that much of the regulatory genetic network controlling the specification and differentiation of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 48 publications
4
101
0
1
Order By: Relevance
“…17 Moreover, recent work suggests that FoxO and KATP channels reduce cardiac ageing and electrical instability in drosophila. 59 Our results thus link tissue stress and expression of Fox and KATP channels into a coherent framework.Other sensors of energy status impact on the expression and function of Foxs. AMP kinase (AMPK) 60 -62 may signal metabolic stress (AMP/ATP ratio) to Fox.…”
mentioning
confidence: 65%
“…17 Moreover, recent work suggests that FoxO and KATP channels reduce cardiac ageing and electrical instability in drosophila. 59 Our results thus link tissue stress and expression of Fox and KATP channels into a coherent framework.Other sensors of energy status impact on the expression and function of Foxs. AMP kinase (AMPK) 60 -62 may signal metabolic stress (AMP/ATP ratio) to Fox.…”
mentioning
confidence: 65%
“…The cardiac proteasomes of the mouse and the fly have been shown to be www.intechopen.com comparable with respect to their overall composition (Cammarato et al, 2011), and functional analysis revealed further evidence of the conserved cardiac characteristics of the fly heart (e.g. Ocorr et al, 2007a;Buechling et al, 2009;Choma et al, 2010). In particular, the contractile and electrical properties have been investigated in the Drosophila heart and found to be remarkably similar in fundamental aspects, such as the contribution of ion channels to heart contraction or the effects of mutations of genes of the myofibrillar apparatus (K. Ocorr, unpublished and Lalevée et al, 2006;Wolf et al, 2006;Ocorr et al, 2007b;Cammarato et al, 2008b;Mery et al, 2008).…”
Section: Exploring Fly Heart Function To Understand Chd-related Cardimentioning
confidence: 96%
“…Une étude pionnière [36] a mis en évidence, que chez la mouche, le vieillissement s'accompagne d'une diminution de la réserve cardiaque 4 et d'une augmentation des arythmies, deux caractéristiques centrales du vieillissement qui sont partagées avec les mammifères. D'autres études [37][38][39] ont depuis largement confirmé ces observations. Elles ont montré que le vieillissement s'accompagne également d'une diminution du débit cardiaque [39,40] et de défauts structuraux au niveau des cardiomyocytes, qui sont liés à une désorga-nisation progressive du réseau de myofibrilles [20].…”
Section: Cardiopathies Et Métabolismeunclassified